A Methodology for Characterizing Lithium-Ion Batteries Under Constant-Current Charging Based on Spectral Analysis - Anatolij Nikonov; Marko Nagode; Jernej Klemenc (World Electric Vehicle Journal)
This study addresses the challenge of gaining a deeper understanding of charging and discharging mechanisms in lithium-ion batteries to enhance their reliability and safety, necessitating the development of novel modeling techniques. A comprehensive analytical model is introduced, capable of accurately reconstructing the voltage rise during constant-current charging. The novelty of this approach lies in its use of spectral analysis (similar to that employed in linear viscoelasticity) to describe the physical processes occurring during battery charging. The model’s effectiveness was validated using experimental data from a rechargeable lithium-ion battery with a nominal capacity of 25 Ah and a nominal voltage of 3.2 V. The results demonstrate that spectral characterization is a reliable tool for modeling battery response to constant-current charging, with the potential for application in battery lifespan prediction.